2003
DOI: 10.1152/ajpheart.00388.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of L-type Ca2+current by C-type natriuretic peptide in bullfrog atrial myocytes: an NPR-C-mediated effect

Abstract: Single atrial myocytes were isolated from the bullfrog heart and studied under current and voltage clamp conditions to determine the electrophysiological effects of the C-type natriuretic peptide (CNP). CNP (10(-8) M) significantly shortened the action potential and reduced its peak amplitude after the application of isoproteronol (10(-7) M). In voltage clamp studies, CNP inhibited isoproteronol-stimulated L-type Ca2+ current (ICa) without any significant effect on the inward rectifier K+ current. The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…Indeed, the E11 ventricular myocardium has been shown to express high levels of NOS and cGMP proteins compared to the E16 myocardium (Ji et al, 1999) and also to respond to muscarinic and adrenergic stimulation . Activation of NPR-C was shown to significantly inhibit ISO induced Ltype Ca 2þ current (LTCC) via the Gi pathway in adult SA nodal, atrial, and ventricular myocytes (Rose et al, 2003(Rose et al, , 2004(Rose et al, , 2005 (Fig. 7A).…”
Section: Gi and Nos Signaling Form The Basis For Functional Heterogenmentioning
confidence: 98%
“…Indeed, the E11 ventricular myocardium has been shown to express high levels of NOS and cGMP proteins compared to the E16 myocardium (Ji et al, 1999) and also to respond to muscarinic and adrenergic stimulation . Activation of NPR-C was shown to significantly inhibit ISO induced Ltype Ca 2þ current (LTCC) via the Gi pathway in adult SA nodal, atrial, and ventricular myocytes (Rose et al, 2003(Rose et al, , 2004(Rose et al, , 2005 (Fig. 7A).…”
Section: Gi and Nos Signaling Form The Basis For Functional Heterogenmentioning
confidence: 98%
“…These measurements demonstrate that neither ANP nor mANP had any effects on mouse atrial AP properties in basal conditions (Figure IB and Tables II and III in the Data Supplement). Because we have previously shown that I Ca,L is a major target of NPs in the atria, 13,15 we also measured the effects of ANP and mANP (100 nmol/L doses) on basal I Ca,L in mouse right atrial myocytes ( Figure IC The absence of effects of ANP on AP morphology and I Ca,L in basal conditions is consistent with our previous studies showing that the related peptides BNP and CNP only affect mouse atrial myocyte electrophysiology in the presence of the β-adrenergic receptor agonist isoproterenol. 13 Accordingly, we next measured the effects of ANP and mANP on AP morphology in mouse atrial myocytes after application of isoproterenol (10 nmol/L).…”
Section: What the Study Addsmentioning
confidence: 99%
“…10 We have recently demonstrated that NPs have potent effects on cardiac electrophysiology. [13][14][15][16] For example, BNP and CNP can increase action potential (AP) duration (APD) in association with increases in L-type Ca 2+ current (I Ca,L ) in atrial myocytes. 13 We have also shown that wild-type NPs (BNP and CNP) can potently increase electrical conduction in the sinoatrial node and atrial myocardium.…”
mentioning
confidence: 99%
“…Voltage-clamp studies demonstrated that CNP can inhibit L-type Ca 2+ current (ICa-L) through NPR-C binding. This inhibition involves a decrease in adenylyl cyclase activity, which leads to reduced intracellular levels of cAMP (Rose et al, 2003). These results were also demonstrated in isolated myocytes from mouse SA node, that express several cAMPsensitive currents, including ICa-L (DiFrancesco, 1993).…”
Section: Natriuretic Peptides (Nps)mentioning
confidence: 71%